2004
DOI: 10.1002/pssb.200304284
|View full text |Cite
|
Sign up to set email alerts
|

Near band edge emission of MBE grown ZnO epilayers: identification of donor impurities and O2 annealing effects

Abstract: Photoluminescence (PL) and selective photoluminescence (SPL) experiments have been carried out to analyse the near band edge emission (NBE) spectra of unintentionally doped ZnO epilayers. It is shown that the different NBE transitions involve donor centres only. The lines can be divided into two groups. Those lying on the low energy side consist of recombinations of neutral-donor bound exciton complexes, while those lying just below the A free excitonic emission correspond to donor-to-valence band transitions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…11,14,15 Although the near-IR emission around 760 nm is sometimes thought to be caused mainly by interstitial zinc, 16 it is more likely to be the second peak of UV emission caused by transitions due to SiÀOÀZn bonds. 12,17,18 The XRD measurements for SnO 2 nanowires (Figure 2b) show main peaks at (110), (101), and (211), and the SnO 2 crystalline structure is tetragonal rutile with lattice constants a = 4.737 Å and c = 3.186 Å (ICDD No. 88-0287).…”
Section: Resultsmentioning
confidence: 99%
“…11,14,15 Although the near-IR emission around 760 nm is sometimes thought to be caused mainly by interstitial zinc, 16 it is more likely to be the second peak of UV emission caused by transitions due to SiÀOÀZn bonds. 12,17,18 The XRD measurements for SnO 2 nanowires (Figure 2b) show main peaks at (110), (101), and (211), and the SnO 2 crystalline structure is tetragonal rutile with lattice constants a = 4.737 Å and c = 3.186 Å (ICDD No. 88-0287).…”
Section: Resultsmentioning
confidence: 99%
“…However, later studies indicated that the I 9 line is actually from excitons bound to In-donors [18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…One of these methods is postgrowth annealing. Annealing has been employed widely for ZnO grown by sputtering, 6,7 molecular beam epitaxy (MBE), 8,9 atomic layer epitaxy, 10 and to ZnO substrates for homo-epitaxial growth 11 to improve the crystalline quality and optical and electrical characteristics for further applications. It has also been employed during the growth process itself to improve the quality of the epilayers.…”
Section: Introductionmentioning
confidence: 99%